A Analysis of Generational Conflict in The Drama Death of Salesman by Arthur Miller’s: Analysis of Generational Conflict in The Drama Death of Salesman by Arthur Miller’s - Azzam al-Mujadid, Muhammad; Nur Ichsan, Praja (Jurnal Pendidikan dan Pengajaran, 2024)
This research explores the generational conflict depicted in Arthur Miller's "Death of a Salesman," focusing on the interplay between Willy Loman and his son Biff. The study, conducted at Sekolah Tinggi Bahasa Asing Technocrat Tangerang, Indonesia, employs dialogue analysis as its primary approach to uncover the implications of differing perspectives on success, identity, and familial ties. The theoretical foundation delves into the dramatic elements of the play, emphasizing the significance of symbols and social identity theory in understanding generational tensions. The research method involves a systematic examination of key dialogues, identifying themes such as generational conflict, success and failure, friendship and loss, and dreams and confusion. The results reveal emotional nuances, linguistic patterns, and the impact of generational conflict on character development. The implications of generational conflict on family dynamics are discussed, highlighting its influence on the relationships within the Loman family. The research contributes to a comprehensive understanding of the play, shedding light on the complexities of generational conflict and its profound effects on character dynamics and the overall narrative structure.